2010
DOI: 10.4141/cjps09035
|View full text |Cite
|
Sign up to set email alerts
|

Gluten index compared with SDS-sedimentation volume for early generation selection for gluten strength in durum wheat

Abstract: . 2010. Gluten index compared with SDSsedimentation volume for early generation selection for gluten strength in durum wheat. Can. J. Plant Sci. 90: 1Á11. Gluten strength is an important end-use quality factor in durum wheat [Triticum turgidum L. ssp. durum (Desf.) Husn.], affecting pasta manufacture and cooking quality. The objective of this research was to determine the inheritance and heritability of gluten index in comparison with the widely used SDS-sedimentation (sodium dodecyl sulphate) technique for se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 43 publications
6
30
2
3
Order By: Relevance
“…These findings are in accordance with the literature (Sissons , Peña and Pfeiffer , Clarke et al. , Rharrabti et al. , Bilgin et al.…”
Section: Discussionsupporting
confidence: 94%
“…These findings are in accordance with the literature (Sissons , Peña and Pfeiffer , Clarke et al. , Rharrabti et al. , Bilgin et al.…”
Section: Discussionsupporting
confidence: 94%
“…The polymeric proteins were also found to have contrastive associations with mixing as well as breadmaking characteristics according to extractability in hard wheat (Ohm et al 2009(Ohm et al , 2010Wrigley et al 2006). This might be owing to the closer positive association between sedimentation volume and protein quantity than other gluten strength parameters (Clarke et al 2010). In the current research, the influence of gliadins was also shown by negative correlations of gluten strength characteristics (such as gluten index and mixograph pattern) with AA and AP values around F2 of the extractable fraction, which is primarily composed of gliadins ( Fig.…”
Section: Resultssupporting
confidence: 57%
“…Sedimentation volume and gluten index provide information on gluten strength and are used as important parameters in durum quality evaluation (Cubadda et al 1992;Clarke et al 2010). Mixograph classification is rated by semolina mixogram pattern, which is also closely associated with gluten characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…Because executing any of these tests requires relatively simple equipment for evaluating several samples concurrently in short periods of time, SIG, LARC, and SDSS might be efficient methods to select for gluten strength in late segregating or early advanced stages. However, there are only a few studies comparing these different small-scale testing methods Kovacs 2002b, 2002c;Gaines et al 2006;Clarke et al 2010). In addition, although the ability of SDSS, SIG, and LARC to screen for gluten strength in early breeding stages is well recognized, limited information is available concerning whether their predicting ability would vary across different environments, particularly in stress environments.…”
Section: Introductionmentioning
confidence: 99%